Outcomes of older patients with primary central nervous system lymphoma treated in routine clinical practice in the UK: methotrexate dose intensity correlates with response and survival. (31st March 2020) - Martinez‐Calle, Nicolás; Poynton, Edward; Alchawaf, Alia; Kassam, Shireen; Horan, Matthew; Rafferty, Mark; Kelsey, Phillipa; Scott, Gemma; Culligan, Dominic J.; Buckley, Hannah; Lim, Yeong J.; Ngu, Loretta; et al.
Summary: Data on older patients with primary central nervous system lymphoma (PCNSL) are scarce. Comorbidities and performance status frequently compromise outcomes in this group. Medical records for consecutive patients ≥65 years ( n  = 244) with PCNSL diagnosed 2012–2017 from 14 UK centres were retrospectively reviewed. Of these 192 patients received methotrexate (MTX)‐based treatment. Patients were categorised based on clinician's treatment choice into 'palliative' ( n  = 52), 'less intensive: MTX ± rituximab ± alkylators' ( n  = 74) and 'intensive: MTX/cytarabine combinations' ( n  = 118) groups. Complete remission (CR) rate, two‐year progression‐free survival (PFS) and overall survival (OS) rates were 49%, 11% and 24% for the less intensive and 69%, 40% and 50% for the intensive groups. Treatment‐related mortality (TRM) was 6·8% for MTX‐treated patients. Median MTX cumulative dose was 8·8 g/m 2 (range 1·5–21) over a median of three cycles. Higher relative dose intensity of MTX (MTX‐RDI) was associated with improved PFS and OS in both groups adjusting for age, Eastern cooperative oncology group (ECOG) score and baseline parameters. Two‐year PFS and OS for patients receiving four or more induction cycles followed by consolidation ( n  = 36) were 65% and 70% respectively. Older patients completing MTX‐based induction and consolidation had clinical outcomes similar to those in younger cohorts. These retrospective data suggest that maximising MTX‐RDI and delivering consolidation in a subgroup of older patients may improve clinical outcomes.